Interactive Theater, an Engaging Knowledge Management Tool for IFC Training! - Saypol, Ben (World Bank, Washington, DC, 2012)
When seeking to engage a community and disseminate critical knowledge and skills, experience points to one of the most innovative, engaging, and effective learning tools available. Interactive Theater has been successfully applied to raise awareness, challenge attitudes, and influence behaviors around a wide variety of issues in diverse settings. Examples include public health and conflict resolution issues in international communities, faculty development issues on university campuses, social justice issues in colleges and high schools, and physician-patient communication in hospitals and medical schools. The question at hand this past spring was: could Interactive Theater be adapted and applied to engage and train stakeholders who work to foster public-private dialogue and private sector development in developing nations? The answer was a resounding 'Yes.' This smart lesson describes how Interactive Theater was successfully used as a learning tool by the Investment Climate Department during two sessions of the 6th annual international workshop on Public-Private Dialogue (PPD) in Vienna, Austria in June 2011.